Encouraging The Potentials of Sustainable Competitive Advantage of Halal-Based Creative Micro, Small, Medium Enterprises on Asean Trade - Afni Regita Cahyani Muis; Suniyyah Puspita Sari; Afifa Nurhaliza; Ida Susilowati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The halal creative sectors have considerable potential for sustainable economic advantage in the Southeast Asian region. As an emerging region that often becomes the world trade hub, ASEAN takes advantage of the capabilities of its member countries toward competitive advantages in creative and rapid halal industry development. Micro, Small, and Medium Enterprises (MSMEs), as the main actors in integrating the halal-based creative industries, play an essential role in developing the halal creative sectors for ASEAN trade. Thus, this research addresses the potential sustainable competitive advantage of halal-based innovative MSMEs for ASEAN trade. This study uses two analytical concepts: sustainable competitive advantage and a halal-based creative economy. Furthermore, the research uses a qualitative-exploratory approach with secondary analysis. The findings of this study are that halal-based innovative MSMEs have the potential for sustainable competitive advantage, which supports the performance of such MSMEs, cultivating and supporting the ASEAN trade.Keywords: Sustainable Competitive Advantage; MSMEs; Trade; ASEAN AbstrakSektor kreatif halal ditegaskan sebagai potensi besar keuntungan ekonomi berkelanjutan di kawasan Asia Tenggara. Sebagai emerging region yang sering menjadi hub perdagangan dunia, ASEAN memanfaatkan kapabilitas negara-negara anggotanya menuju keunggulan kompetitif dalam perkembangan industri halal yang kreatif dan pesat. Usaha Mikro, Kecil, Menengah (UMKM) sebagai pelaku utama dalam mengintegrasikan industri kreatif berbasis halal berperan penting untuk mengembangkan sektor kreatif halal bagi perdagangan ASEAN. Dengan demikian, penelitian ini ditujukan untuk mengatasi potensi keunggulan kompetitif yang berkelanjutan dari UMKM kreatif berbasis halal untuk perdagangan ASEAN. Kajian ini menggunakan dua konsep analisis, yaitu keunggulan bersaing berkelanjutan, dan ekonomi kreatif berbasis halal. Penelitian ini menggunakan pendekatan kualitatif-eksploratif dengan analisis sekunder. Temuan dari penelitian ini adalah bahwa UMKM kreatif berbasis halal memiliki potensi keunggulan kompetitif yang berkelanjutan, yang mendukung kinerja UMKM tersebut, budidaya dalam mendukung perdagangan ASEAN.Kata Kunci: Keunggulan Bersaing Berkelanjutan; UMKM; Berdagang; ASEAN